Impact of COVID-19 pandemic on maternity services and challenges faced by pregnant women delivering at a tertiary care centre in South India - Naik, Parvathi Teja; Murugan, Rupesh Bala; Sagili, Haritha; Lakshminarayanan, Subitha; Muruganandhan, Priyadarshini; Puliyullaveettil, Aishwarya Thalappan; Rajaa, Sathish; Radhakrishnan, Sujithra Devi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Coronavirus disease 2019 (COVID-19), was declared a pandemic by the World Health Organization (WHO) on March 11, 2020. India entered a nationwide lockdown on March 25, 2020, disrupting regular health services. Hence this study was conducted to estimate the impact of the COVID-19 pandemic on maternity services and to describe the challenges faced by pregnant women. Methods: A descriptive cross-sectional study conducted from July 2020 to October 2020 at tertiary care hospital, Puducherry, India. 422 pregnant women delivered during this period were included and detailed questionnaire was administered regarding antenatal, intrapartum, postnatal services and, challenges faced during the pandemic via telephonic call. Responses were documented in Epicollect version 5, transferred to Microsoft excel and analysed using Stata version 14.2. Continuous variables were expressed as mean (SD), and Categorical variables as proportions. Results: The 100% response rate was achieved with 32.5% high risk pregnancies. The 71.8% women availed direct emergency medical services while 28.2%. were referrals. The 79.9% and 25% of the women in third trimester had less antenatal visits and discontinued haematinics respectively. The 47.4% had first trimester testing, 30% didn’t receive lactation support. 81% and 69% of primiparous and multiparous women respectively had adopted postpartum Intrauterine contraceptive device as contraception. The 35-50% women faced challenges in availing essential obstetric care services. Conclusions: Development of robust linkage system between existing primary healthcare and tertiary care for managing both low and high-risk pregnancies is of paramount importance to alleviate maternal and perinatal mortality and morbidity.